2016
DOI: 10.5154/r.rchscfa.2015.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Series de incremento del área basal en árboles dominantes de Pseudotsuga menziesii (Mirb.) Franco muestran periodicidad de acuerdo con patrones climáticos globales

Abstract: Basal area increment series of dominant trees oftrunk section allow the analysis of tree growth trajectories. In this study, we used direct measurements of basal area increment (BAI) to explain biological periodicity and forecast basal area growth of Douglas-fir growing in Western Mexico. To remove the age effect on tree growth we also ran the analysis in terms of cambial age. Results showed significant (P < 0.05) correlation between BAI and precipitation from January to July. We found periodicities in tree gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
4
0
7
Order By: Relevance
“…Favorable winter conditions may also improve photosynthesis and increase the reserves of carbohydrates later used in the growing season [33]. These ideas agree with similar results in other studies showing a positive correlation between winter precipitation and radial growth [33,34,42]. Bickford et al [31] also indicated that tree growth in dry areas from N. Mexico is mainly limited by low winter precipitation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Favorable winter conditions may also improve photosynthesis and increase the reserves of carbohydrates later used in the growing season [33]. These ideas agree with similar results in other studies showing a positive correlation between winter precipitation and radial growth [33,34,42]. Bickford et al [31] also indicated that tree growth in dry areas from N. Mexico is mainly limited by low winter precipitation.…”
Section: Discussionsupporting
confidence: 77%
“…As a consequence, the capacity of the response in growth to the hydroclimatic variability could be used as an indicator of forest vulnerability to drought [9], and these responses could be used to forecast growth and productivity responses to climate change [34].…”
Section: Discussionmentioning
confidence: 99%
“…hartwegii forest. Here our sampling procedure of trees was based on dominant trees, more than in water or nutrient stressed individuals as suggested in the dendroclimatology approach (Fritts, ); thus, trees with position at the highest canopy level were effective to capture tree growth dynamics, as in others works (Berner et al, ; Castruita‐Esparza et al, ). Temperature is a determinant factor for tree growth at alpine and boreal forests, triggering the reactivation of cambial activity, xylem cell differentiation, and photosynthesis (Antonucci et al, ; Körner & Paulsen, ; Li et al, ; Rossi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although Astudillo-Sánchez et al (2017) developed a chronology in the same mountain, our new ring width chronology is an updated series 50 years longer with a stronger sample depth support, useful to describe the tree growth variation for this P. hartwegii forest. Here our sampling procedure of trees was based on dominant trees, more than in water or nutrient stressed individuals as suggested in the dendroclimatology approach (Fritts, 1976); thus, trees with position at the highest canopy level were effective to capture tree growth dynamics, as in others works Castruita-Esparza et al, 2016). Temperature is a determinant factor for tree growth at alpine and boreal forests, triggering the reactivation Figure 10.…”
Section: Forest Growth At High-elevation Forestmentioning
confidence: 99%
See 1 more Smart Citation